THE IMPACT OF THE QUESTION ANSWER RELATIONSHIP (QAR) STRATEGY ON IMPROVING STUDENTS’ READING COMPREHENSION - Gaffar, Muhammad Andriana; Aini, Hasna Qurrotul; Hidayah, Lutfiah; Maulana, Ryfo Juan (University of Kuningan, 2024)
Abstract: This study investigates the impact of the Question Answer Relationship (QAR) strategy on improving reading comprehension among ninth-grade students’. This rerserarch was urtilizing stratergy is qurantitativer rerserarch by applying prer-erxperrimerntal rerserarch. This study uses research techniques grourp irrergurlar tersting or random sampling. This rerserarch was urserd oner grourp discurssion dersign. A pre-eksperimental design with pre-test and post-test was employed on a sample of 30 ninth-grade students at MTs An-Namiroh. Data was collercterd throurgh a terst on rerading comprerhernsion. Ther data was rerqurirerd by condurcting murltipler choicer terst consisterd of 10 iterms. Ther hypothersis of ther QAR stratergy ursing ther pairerd simpler terst bertwerern ther prer-terst and post-terst shows differrernt rersurlts, that ther sturdernts' scorers increraserd in ther post-terst. Ther pairerd sampler terst was urserd to ervalurater ther data, and p<0,05 was urserd to asserss significancer. Results indicate a significant improvement in students’ reading comprehension after the implementation of the QAR strategy. Ther findings show that, at a significant thrershold of 0,05, therrer was a statistically significant differrerncer ther sturdernts’ rerading comprerhernsion achiervermernt. These findings suggest that the QAR strategy can effectively enhance reading comprehension in junior high school students.Keywords: Qurerstion Answerr Rerlationship (QAR) Stratergy, Sturdernts’ Rerading Skills, Rerading Comprerhernsion